Soil sampling and sample preparation - Pleysier, J.L. (1995)
The approach to soil sampling depends on the reasons for soil analysis. Soil is not a homogeneous mass. Plant life, topography, agronomic practices, etc. affect the uniformity of a soil. The accuracy of the soil analysis data depends on the accuracy with which the soil samples are taken. Several definitions and terms are important to describe fertilizers. The "grade", for example, describe the N-P205-K20 content in weight percentage. The exact amount of fertilizer required has to be calculated depending on type of fertilizer and area to be fertilized. Mixing of fertilizers makes application easier, however, not all fertilizers can be mixed.